TRADITIONAL-CONTEMPORARY’ COMMUNITY ENGAGEMENT APPROACHES FOR EFFECTIVE LOCAL CLIMATE CHANGE ADAPTATION IN INDONESIA - Meuthia Naim; Richard Hindmarsh (Pusat Standardisasi Instrumen Kualitas Lingkungan Hidup Laboratorium Lingkungan (P3KLL), 2019)
The current problem of inadequate (or ineffective) community engagement in Indonesia poses a major policy gap for the Indonesian endeavour to develop effective climate change adaptation. This gap needs addressing for robust adaptation to occur in a country highly vulnerable to extreme weather events and changing weather patterns. Currently, 65% of the Indonesian population (of some 265 million) reside on the coast with many dependent upon natural resources for their livelihoods. As climate change strengthens, effective participatory climate change adaptation – here with the focus on inclusive and active local community engagement – needs development as a priority to reduce the high vulnerability of communities and to achieve resilient communities. To close this policy gap – as informed by historical analysis, archival materials, and interview data – we posit that local community engagement approaches that integrate traditional and contemporary (or “old” and “new”) engagement practices and approaches offer much promise for local community adaptation effectiveness in the case of Indonesia. Such approaches we also posit should have relevance for other traditional-contemporary informed societies, as most evident in developing countries.